Simulation of coastal flood in Kuantan City using ARC-GIS - Nurul Ain Syazwani, Ahmad Azman (2017)
Coastal flood is formed of tides event, sea level rise and storm surge event, overflow from the sea and inundated the lower area below the height range of coastal flood especially in the coastlines area. Coastal flood also is one of the catastrophe that could cause loss of life and property if there is no awareness among the population around the coast. Therefore, local agencies should start to find some solutions to prevent this severe flood. One of the effective ways to overcome this problem is by using ArcGIS software. ArcGIS software or well known as Geographical Information System (GIS) is a computer system for capturing, storing, checking, and displaying data related to the position on Earth’s surface. The objectives of this study are to find the risky location in Kuantan City that was affected by the coastal flood for the next 50 and 100 years and to propose the mitigation plans. Kuantan City was selected as a study area. This study was formed because the location of Kuantan City was exposed to the risk of coastal flood. The data used for this study was provided from National Hydraulic Research Institute of Malaysia (NAHRIM), Jabatan Ukur dan Pemetaan Malaysia (JUPEM), Malaysian Meteorological Department (MetMalaysia), National Hydrographic Centre Malaysia (NHC) and also from the research papers. The needed data were tide gauge data, storm surge data and sea level rise data in projected years. In this study, Arc Map and Arc Scene was used to analyse all the data hence provide coastal flood map that could able to identify the affected areas. ArcMap was used to produce three different types coastal flood map; coastal flood map in year 2050 (8.46 meter), coastal flood map in year 2100 (8.72 meter) and coastal flood map in 5 meter height of seawater. The results of coastal flood map were presented in the Google Earth and all affected location were classified from JUPEM topographical map. This coastal flood map will be facilitate a lot of parties whether the government nor the people around the coast to be alert to the presence of coastal flood. In additional, the mitigation plans has also been set up to prevent this problem hence save the coastal ecosystems. This study also has proved that the coastal flood could be predicted thus various initiatives or measure precaution should be taken when this natural disaster happen.